2021
DOI: 10.1016/j.heliyon.2021.e07187
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive composition, free radical scavenging and fatty acid profile of Ximenia americana grown in Ethiopia

Abstract: Ximenia americana is among wild edible fruit indigenous to Ethiopia. The fruit reported as indispensable source of phytochemicals and health imparting components. However, the phytochemicals constituents, antioxidant activities and fatty acid profile of Ethiopian X. americana cultivar studies are still scarce. This research aimed at evaluation of flesh and seed of Ethiopian X. americana yellow and red colored cultivars for bioactive component, antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Similar medicinal uses of these plants have been widely reported in different parts of the country. 14 , 17 , 25 , 54 , 71 , 86 , 88 , 98 , 188 Among the medicinal plants claimed to manage livestock health problems, Ekebergia capensis and Datura stramonium which are used against babesiosis and rabies, respectively, scored the highest FL and ROP values. Previous studies have also reported the anti-infectious properties.…”
Section: Discussionmentioning
confidence: 99%
“…Similar medicinal uses of these plants have been widely reported in different parts of the country. 14 , 17 , 25 , 54 , 71 , 86 , 88 , 98 , 188 Among the medicinal plants claimed to manage livestock health problems, Ekebergia capensis and Datura stramonium which are used against babesiosis and rabies, respectively, scored the highest FL and ROP values. Previous studies have also reported the anti-infectious properties.…”
Section: Discussionmentioning
confidence: 99%
“…The cookies sample was extracted using soaking extraction according to the methods documented by Msaddak et al [ 25 ], and Bazezew et al [ 26 ], with some modification. According to this, the cookies samples were made into fine powder using pestle and mortar.…”
Section: Methodsmentioning
confidence: 99%
“…An inorganic residue that reflects the entire amount of minerals in food is ash (39). A higher ash concentration predicts the existence of a variety of mineral components (40). Ash concentration ranged from 0.99 to 4.95%, with Elatostema sp.…”
Section: Nutritional Qualitymentioning
confidence: 99%